Response of Soil Fertility and Bacterial Community Composition to Vegetation Species in a Coal Mining Subsidence Area: A Survey After 20-Year Reclamation - Wang, Yuming; Fan, Yuchao; Wang, Qiuya; Zhang, Shiwen; Shi, Yu; Zheng, Xuebo (Frontiers in Environmental Science, 2022)
Revegetation is an important restoration approach after reclamation in coal mining subsidence area. However, few studies have paid attention to the impacts of different vegetation species on soil fertility and bacterial community composition in the reclamation area filled with fly ash for a long time. In this study, soil fertility and bacterial community composition were investigated in a non-subsidence area (FCK) and a coal mining subsidence reclamation area restored vegetation with woody plants (pagoda trees, FS; peach trees, FP) and herbaceous plants (wheat-maize rotation, FW) for 20 years. Results showed that topsoil and subsoil nutrients including available K and alkali-hydrolyzable N, soil organic matter, and total carbon in the non-subsidence site were significantly higher than those in reclamation sites. Topsoil fertility indices (SFI) in reclamation sites were lower than that in non-subsidence site, and SFI in FW was higher than that in FS and FP. Moreover, the SFI in topsoil (from –0.24 to 2.08) was significantly higher than that in subsoil (from –1.12 to –0.39). 16S rRNA gene sequencing analysis showed Proteobacteria, Acidobacteria and Actinobacteria were the dominant bacterial phyla in all sites, but the subsoil bacterial alpha indices (Shannon and Simpson) in the non-subsidence site were higher than those in reclamation sites. Principal coordinates analysis and non-metric multidimensional scaling analysis showed that the bacterial community composition in reclamation sites was significantly different from that in the non-subsidence site, and they were similar in the soil with wheat-maize rotation model between non-subsidence and reclamation sites. Co-occurrence network analysis noted that the network of dominant bacterial operational taxonomic units in the subsoil was more complex than that in the topsoil. Redundancy analysis suggested soil pH in topsoil and subsoil was an important driving factor for soil bacteria community composition. Overall, the reclamation site with the wheat-maize rotation model had higher soil fertility and bacterial community composition was similar to that of the non-subsidence site, indicating revegetation with the wheat-maize rotation model is a good reclamation approach to improve soil fertility in coal mining subsidence area.